2011
DOI: 10.1262/jrd.11-066h
|View full text |Cite
|
Sign up to set email alerts
|

High Developmental Rates of Mouse Oocytes Cryopreserved by an Optimized Vitrification Protocol: The Effects of Cryoprotectants, Calcium and Cumulus Cells

Abstract: Unfertilized oocytes are one of the most desired germ cell stages for cryopreservation because these cryopreserved oocytes can be used for assisted reproductive technologies, including in vitro fertilization (IVF) and intracytoplasmic sperm injection. However, in general, the fertility and developmental ability of cryopreserved oocytes are still low. The aim of the present study was to improve vitrification of mouse oocytes. First, the effects of calcium and cryoprotectants, dimethyl sulfoxide and ethylene gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 33 publications
(52 reference statements)
0
47
0
2
Order By: Relevance
“…There are some reports about the vitrification of mouse oocytes [13][14][15]28,37]. Seki and Mazur yields high survival of vitrifiedwarmed ICR mouse oocytes using the Cryotop with ultra-rapid warming (117,000°C/min) [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some reports about the vitrification of mouse oocytes [13][14][15]28,37]. Seki and Mazur yields high survival of vitrifiedwarmed ICR mouse oocytes using the Cryotop with ultra-rapid warming (117,000°C/min) [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, although many papers concerning the cryopreservation of mouse oocytes have been published since the first successful reports of oocyte freezing [24,36], a simple and practical freezing method for unfertilized C57BL/6 mouse oocytes, and an IVF system using these cryopreserved oocytes have yet to be established [13,14,18,20,21,29]. There is a strong need to develop a technology of oocyte cryopreservation of C57BL/6 mouse and IVF using the oocytes for efficiently producing GEM in the animal facility.…”
Section: Introductionmentioning
confidence: 99%
“…2 The red fluorescence images on LSCM of human MII oocyte stained by JC-1. 2A, 2B, 2C and 2D represents the typical distribution of red fluorescence in fresh, cultured for 0 h, 2 h and 4 h oocytes after vitrification/thawing, respectively be the ideal cryoprotectant for oocytes and embryo vitrification [24], and it could retain oocytes developmental competence better than DMSO [25]. Moreover, it has been reported that cryoprotectant mixtures may have some advantage over solutions containing only one permeable cryoprotectant, since PROH and sugar exert major influences on the vitrification properties of ethylene glycol-based solutions and have low toxicity to embryos and oocytes [26].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that compared to DMSO, EG had a lesser toxic effect on the vitrification of unfertilized oocytes in mice [17]. It was also suggested that the current CPAs, even EG, have toxic effects on cell viability in a dose-dependent manner [18], indicating that the development of a new CPA showing high efficiency and low toxicity is necessary for further improvements in vitrification.…”
Section: Introductionmentioning
confidence: 99%